Biodegradable Plastic Synthesis from Sapodilla Fruit Starch (Manilkara zapota): Effects of Chitosan Ratio and Glycerol Concentration - Muhammad Faizulhaq; Rofik Wahyu Hidayat; Ayu Pita Kurniasari (Journal of Vocational Studies on Applied Research, 2025)
The productivity of Majalengka sapodilla production has declined, posing significant challenges for sapodilla farmers. This issue is further compounded by the fluctuating availability of land for sapodilla cultivation. Given its nutritional composition, sapodilla fruit holds potential for development into a biodegradable product by utilizing its starch in conjunction with chitosan. The aim of developing this biodegradable product is to reduce the reliance on synthetic plastic for packaging processed foods. This study investigated the water, fat, and protein content in sapodilla fruit, as well as the characteristics of the resulting biodegradable material. The sapodilla starch content was found to be 9%, with a water content of 2%, a fat content of 0.5%, and a protein content of 12.44%. The biodegradable material exhibited a maximum thickness of 0.354 mm at a sapodilla starch to chitosan ratio of 30%:70% with 100% glycerol plasticizer. The maximum degradability percentage achieved was 85.7% at a starch to chitosan ratio of 60%:40% with 100% glycerol. From the degradability tests of sapodilla starch and chitosan biodegradable plastic with glycerol plasticizer, it can be concluded that the optimum degradability value is 88.2% for samples with a starch to chitosan ratio of 60%:40% and a glycerol volume of 100%. This indicates that increasing the volume of glycerol and starch enhances the biodegradable capability.